Dilema dan Aspirasi Mohja Kahf Sebagai Muslimah Arab-Amerika Seperti Tertuang dalam Kumpulan Puisinya yang Berjudul Emails from Scheherazad - Febriyanti Dwiratna Lestari (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2013)
Being an Arab-American Muslim woman in America, Mohja Kahf has encountered not only problems in living a life which is in accordance with Islamic sharia but also the difficulties to deal with non-Muslim Americans who are often cynical with Muslim’s dress, rituals and so forth. As a poet, she expresses all her thought, feeling, hope, and anxiety in her poem collection Emails from Scheherazad (2003). This research attempts to elaborate both dilemma and aspiration of Kahf as an Arab-American Muslim woman as figured out in a number of her poems in Emails from Scheherazad. This is a qualitative research, and it approaches the poems using sociology of literature theory. Thus, it analyzes not only the issues within the poems but also cross-checks it with the relevant social subjects such as the existence of Arab-American Muslim in America, the response of American government and society towards Muslim’s way of life in America, and brief account on Kahf’s life. This research has found that the dilemmas faced by Kahf are mostly those related with wearing a scarf, performing Salah starting from descent facilities for wudu to prayer. Also, Kahf aspires for love, friendship, strong commitment to ancestor’s tradition while peacefully conforming to present locale, and humanity above all.